Impact of transmission tower-line interaction to the bulk power system during hurricane. (November 2020) - Xue, Jiayue; Mohammadi, Farshad; Li, Xin; Sahraei-Ardakani, Mostafa; Ou, Ge; Pu, Zhaoxia
Highlights: Predicted power system performance and outage during a hurricane considering the physical impact of transmission tower-line interaction. Developed a wind fragility model of the tower-line system under tower-line interaction by a computationally efficient approach. Evaluated the performance of Texas 2000-bus power network during Hurricane Harvey to investigate the effectiveness of the fragility model. The estimated damage in the power system matches with Hurricane Harvey event analysis report by NERC. Abstract: A Hurricane is a severe weather event that has caused massive blackouts in the United States. Previous studies about a hurricane's impact on the power system were mainly conducted through statistical analysis. However, there is limited research that reveals the physical law governing power outage and system-level performance. Therefore, this paper investigates the impact of transmission tower damage and failure on the performance of the power transmission network during a hurricane. To translate meteorological information to the input of the abstract power network, a fragility model of a transmission tower-line considering the coupling effect is developed. The computational efficiency in the fragility analysis is enhanced by wind speed convention and sample size selection. The effectiveness of the fragility model is investigated in a benchmark problem, which evaluates the performance of a synthetic transmission system (Texas 2000-bus power network) during Hurricane Harvey. The promising results indicate that: (1) from both the element and system level, the coupling effect between the transmission tower-line system is not negligible; (2) the computational efficiency of the fragility analysis can be significantly improved by wind speed conversion and sample size selection; (3) considering the tower-line interaction, the estimated damage to the power system matches the recorded damage from Hurricane Harvey.